2017
DOI: 10.1152/ajpgi.00426.2016
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NEAT1 promotes hepatocellular carcinoma cell proliferation through the regulation of miR-129-5p-VCP-IκB

Abstract: Long non-coding RNA nuclear-enriched abundant transcript 1 (NEAT1) plays an important role in the pathogenesis and development of several types of cancer. However, the functional mechanism of NEAT1 in hepatocellular carcinoma (HCC) remains unclear. NEAT1 and microRNA (miR)-129-5p expression in HCC tissues and cell lines was quantified by means of quantitative PCR. The effects of NEAT1 expression inhibition or upregulation in HCC cell lines were analyzed in terms of cell viability and apoptosis. Biological soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 24 publications
5
66
0
Order By: Relevance
“…30 Our study showed that there was negative significant correlation between the relative expression level of serum LNC NEAT and MiR-129-5p in HCC group (p < .0001). This was coincided previously by Fang et al 31 Several studies demonstrated the role of lncRNAs in regulating the biological role of miRNA. 32 Huibing et al found that NEAT1 has a role in renal cell carcinoma through regulation of MiR-129-5p.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…30 Our study showed that there was negative significant correlation between the relative expression level of serum LNC NEAT and MiR-129-5p in HCC group (p < .0001). This was coincided previously by Fang et al 31 Several studies demonstrated the role of lncRNAs in regulating the biological role of miRNA. 32 Huibing et al found that NEAT1 has a role in renal cell carcinoma through regulation of MiR-129-5p.…”
Section: Discussionsupporting
confidence: 87%
“…Huibing et al found that NEAT1 has a role in renal cell carcinoma through regulation of MiR‐129‐5p . Also a study done by Fang et al showed that LNC NEAT1 by regulation of miR‐129‐5p‐VCP‐I k B could proliferate hepatic cancer …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that NEAT1 epigenetically silenced miR-129-5p expression by promoting DNA methylation of the CpG island in the miR-129 gene in breast tumorigenesis, thus resulting in an upregulation of WNT4 expression, a target of miR-129-5p [22]. Moreover, overexpression of NEAT1 inhibited the expression of miR-129-5p in hepatocellular carcinoma by regulating its targets, namely, valosin-containing protein (VCP) and inhibitor of kappa B (I κ B) [23].…”
Section: Introductionmentioning
confidence: 99%
“…NEAT1 is a kind of lncRNA located on chromosome 11 (11q13.1), which can play critical roles and promote various human cancers tumorigenesis (Fang, Sun, et al, ). NEAT1 can function as a vital component of nuclear paraspeckles structure (Clemson et al, ; Sasaki, Ideue, Sano, Mituyama, & Hirose, ).…”
Section: Discussionmentioning
confidence: 99%